Superior reaction to changing directions for skilled basketball defenders but not linked with specialised anticipation - Fujii, K.; Shinya, M.; Yamashita, D.; Oda, S.; Kouzaki, M. (European Journal of Sport Science, 2014)
The purpose of the present study was to examine the timing for the detection of relevant information in the final running direction of attackers' cutting manoeuvres. Skilled basketball players and novices performed sidestep and reach tasks in response to a ready-go choice stimuli using light-emitting diode (LED) task and video stimuli (video task) wherein skilled ball players executed cutting manoeuvres. The time at which the defenders first obtained relevant visual information was estimated by subtracting the visuo-motor processing time, acquired from the reaction time in the LED task, from the reaction time in the video task. Skilled basketball players reacted to and reached towards the target faster than novices, whereas the estimated video cue timings for the skilled players were not different from those for the novices. The results suggest that the anticipation of attacker's direction in this task would be a general visuo-motor skill, even without previous specialised perceptual training. Combined with the results from the reaction performance in the video task, we conclude that novices are afforded shorter times and more uncertain information before their stepping when they are in a one-on-one ballgame defensive scenario because their sidestepping takes a relatively long time.